DAMPAK KEBERADAAN KAPAL PENYAMBANG TERHADAP PERTUMBUHAN KAWASAN EKONOMI PERIKANAN DI PELABUHAN PERIKANAN MUARA KINTAP KABUPATEN TANAH LAUT - Martiah Akhdianti; Idiannor Mahyudin Mahyudin; Tri Dekayanti (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
Kintap coastal area is one of the areas that developed as a coastal fishery production. Area-based coastal fisheries as Kintap Muara district is consisting of the main activities of fishing activity in the form of Fish Landing Base (PPI) with a variety of amenities. Coastal areas in the village of Muara Kintap pattern fisheries are people who are known to pattern middlemen (Indonesian : penyambang) and developed since 2003. Study was conducted to see how the existence determines penyambang ships for fishing communities and the fishing estuary fishing port Kintap with : identifying the impact of fishing communities penyambang vessel catch and fishing port Muara Kintap; analyze business profits as penyambang ship; formulate strategy development as a fishing port economic zone fisheries. Technique uses qualitative and quantitative methods with a descriptive approach.The existence of the ship penyambang was a positive impact on fishermen catch. Fishermen catch will work more effectively and provide capital as a form of business development, while for the Port of Muara Kintap, penyambang ship has negatif impact on the port becauses penyambang ship can not be loading and unloading in theport. So that data from the catches of fishermen willnot be sould to penyambang as data the basis for determining the policy is difficult to know and retribution for PAD port no. Average profit businesses penyambang vessel during fishing season is Rp.2.773.611,00 per month while the crew (ABK) get Rp.1.386.806, 00 per month and crew still above the local minimum wage (UMR) South Kalimantan Province of Rp.1.337.500.00.Fishing harbor in the village of Muara Kintap, Tanah Laut District as district fisheries economy still needs a better development strategy so that the presence of the ship penyambang can contribute to Improved Income (PAD) Kintap Estuary Fishery Port.